Grown : a novel - Jackson, Tiffany D. (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2020)
"When legendary R&B artist Korey Fields spots Enchanted Jones at an audition, her dreams of being a famous singer take flight. Until Enchanted wakes up with blood on her hands and zero memory of the previous night. Who killed Korey Fields? Before there was a dead body, Enchanted's dreams had turned into a nightmare. Because behind Korey's charm and star power was a controlling dark side. Now he's dead, the police are at the door, and all signs point to Enchanted"--